2020
DOI: 10.2147/prbm.s242699
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effects of Racial/Ethnic Minority Status on Sleep, Mood Disturbance, and Depression in People with Fibromyalgia</p>

Abstract: Purpose: Fibromyalgia syndrome (FMS) is a chronic musculoskeletal pain disorder that is characterized by persistent and widespread pain. FMS has been associated with sleep disturbance, mood disorders and depression. Racial/ethnic minorities are less likely to receive a diagnosis of FMS than White individuals. Although mood disorders and depression are prevalent among racial/ethnic minority groups, researchers have not examined whether there are differences between racial/ethnic minorities and White individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…However, in the FM group, White participants were more depressed than non-White participants. Marr et al [ 28 ] reported similar findings. In their study, they found that racial and ethnic minorities experienced greater depression, mood disturbances, pain, and poorer health than their White counterparts.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, in the FM group, White participants were more depressed than non-White participants. Marr et al [ 28 ] reported similar findings. In their study, they found that racial and ethnic minorities experienced greater depression, mood disturbances, pain, and poorer health than their White counterparts.…”
Section: Discussionsupporting
confidence: 57%
“…As with other chronic conditions, people with FM and OA often experience psychological difficulties and report higher rates of depression than those in the general population [ 21 , 22 , 23 , 24 , 25 ]. To study depression in people with these illnesses, researchers have investigated various health, psychological and demographic predictors of depression [ 26 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mood disturbances, including symptoms associated with anxiety and depression, have been increasing in prevalence in the population ( 1 – 3 ), and this has been exacerbated greatly due to lockdowns, social isolation, economic and health-related concerns during the COVID-19 pandemic ( 4 – 6 ). Problems of mood may be transitory, but they affect persons of all ages, gender, social class, and cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Fibromyalgia is a condition where 90% of enrolled subjects are women [ 12 ] and has a higher prevalence in minority populations [ 13 ]. Moreover, racial/ethnic minorities report significantly greater levels of symptoms [ 14 ]. Fibromyalgia is a debilitating, poorly understood, and complex chronic pain condition [ 15 ], where most patients are highly impacted by the disease, lacking access to healthcare delivery and suffering significant comorbidities, such as functional and psychiatry disorders [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%